Pengaruh Literasi Keuangan dan Gaya Hidup terhadap Pembayaran Digital, dengan Penggunaan Teknologi Keuangan sebagai Variabel Intervening pada Mahasiswa Bisnis Digital Universitas Jambi Angkatan 2021 – 2024 - Dhimas Kurniawan; Tona Aurora Lubis; Ida Masriani (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of financial literacy and lifestyle on digital payments with the use of financial technology as an intervening variable for Jambi University digital business students Class of 2021 - 2024. This study uses a quantitative approach with a random sampling method. The population in this study, namely Jambi University digital business students in the 2021-2024 batch of 174 students and the sample of this study amounted to 64 students. The data collection technique used a questionnaire. The data analysis method in this study used Patrial Least Square and was processed using smartPLS 4.0 software. The results of this study found that: 1) Financial literacy has a positive and significant effect on digital payments. 2) Lifestyle has a positive and insignificant effect on digital payments. 3) Financial Literacy has a positive and significant effect on the use of financial technology. 4) Lifestyle has a positive and significant effect on the use of financial technology. 5) the use of financial technology has a positive effect on digital payments. 6) Financial Literacy has a positive and significant effect on digital payments with the use of financial technology as an intervening variable. 7) Lifestyle has a positive and insignificant effect on digital payments with the use of financial technology as an intervening variable.